PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Warnet Pengguna Telkom Speedy di Kecamatan Siantar Timur) - Rico, Rico; Lie, Darwin; Butarbutar, Marisi; Wijaya, Andy (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The results of the study can be concluded as follows: 1. The quality of the product is quite good, quite good brand image, purchasing decisions are quite agree and consumer satisfaction was quite satisfied. 2. There is a positive influence between product quality and consumer satisfaction toward purchasing decisions is evidenced by the regression Å¶(Z) = 5,399 + 0,328 X 1 + 0,414 X 2. There is a positive influence between purchase decisions against consumer satisfaction evidenced by regression Å¶ = 34,089 + 0,352 X(Z). 3. There is moderately high and positive correlation between product quality and brand image against a decision of purchase evidenced by r = 0,794 with R Square = 61.3%. There is a low and positive correlation between the buying decision towards customer satisfaction is evidenced by the r = 0,360 with R Square = 12.9%. 4. The results of the hypothesis H0 is rejected, meaning that product quality and brand image a positive and significant effect against the satisfaction of consumers through the buying decision as simultaneously intervening variables as well as partial.As for the suggestion of this research are: 1. To improve the quality of the product we recommend that you add to the access speed and improve the durability of Telkom Speedy modem. 2. To enhance the brand image of Telkom Speedy should improve product quality and establish good relationships with consumers. 3. To enhance the purchasing decision Telkom Speedy should lower prices and costs. 4. To increase consumer satisfaction Telkom Speedy should give maximum service and improve the quality of the product.Â Keyword: Product Quality, Brand Image, Purchasing Decisions and Consumer Satisfaction.